Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Ask your questions and receive precise answers from experienced professionals across different disciplines. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Absolutely! Let's start with the given quadratic equation and solve it step-by-step.
The given equation is:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
### Step 1: Factoring the Quadratic Equation
To factor this quadratic equation, we need to find two numbers that multiply to the constant term [tex]\(8\)[/tex] and add up to the coefficient of the linear term [tex]\(6\)[/tex].
Let's find such numbers:
- The constant term ([tex]\(c\)[/tex]) is [tex]\(8\)[/tex].
- The coefficient of the linear term ([tex]\(b\)[/tex]) is [tex]\(6\)[/tex].
We need two numbers [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that:
[tex]\[ a \cdot b = 8 \][/tex]
[tex]\[ a + b = 6 \][/tex]
Testing possible factor pairs of [tex]\(8\)[/tex]:
- [tex]\(1 \cdot 8 = 8\)[/tex] and [tex]\(1 + 8 = 9\)[/tex] (does not work)
- [tex]\(2 \cdot 4 = 8\)[/tex] and [tex]\(2 + 4 = 6\)[/tex] (these are the correct numbers!)
So, the numbers that work are [tex]\(2\)[/tex] and [tex]\(4\)[/tex].
We can now write the quadratic expression as a product of two binomials:
[tex]\[ x^2 + 6x + 8 = (x + 2)(x + 4) = 0 \][/tex]
### Step 2: Solving for [tex]\(x\)[/tex]
Now, set each binomial equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x + 2 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Solving these equations:
[tex]\[ x = -2 \quad \text{and} \quad x = -4 \][/tex]
Thus, the [tex]\(x\)[/tex]-intercepts are:
[tex]\[ x = -2 \quad \text{and} \quad x = -4 \][/tex]
### Step 3: Stating the [tex]\(y\)[/tex]-Intercept
The [tex]\(y\)[/tex]-intercept of a function is the point where the graph intersects the [tex]\(y\)[/tex]-axis. This occurs when [tex]\(x = 0\)[/tex].
To find the [tex]\(y\)[/tex]-intercept, substitute [tex]\(x = 0\)[/tex] into the original equation:
[tex]\[ y = 0^2 + 6(0) + 8 = 8 \][/tex]
So, the [tex]\(y\)[/tex]-intercept is:
[tex]\[ 8 \][/tex]
### Summary
- The [tex]\(x\)[/tex]-intercepts are [tex]\(-4\)[/tex] and [tex]\(-2\)[/tex].
- The [tex]\(y\)[/tex]-intercept is [tex]\(8\)[/tex].
Thus, the detailed solutions are:
- [tex]\( x\)[/tex]-intercepts: [tex]\(-4\)[/tex] and [tex]\(-2\)[/tex]
- [tex]\( y\)[/tex]-intercept: [tex]\(8\)[/tex]
The given equation is:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
### Step 1: Factoring the Quadratic Equation
To factor this quadratic equation, we need to find two numbers that multiply to the constant term [tex]\(8\)[/tex] and add up to the coefficient of the linear term [tex]\(6\)[/tex].
Let's find such numbers:
- The constant term ([tex]\(c\)[/tex]) is [tex]\(8\)[/tex].
- The coefficient of the linear term ([tex]\(b\)[/tex]) is [tex]\(6\)[/tex].
We need two numbers [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that:
[tex]\[ a \cdot b = 8 \][/tex]
[tex]\[ a + b = 6 \][/tex]
Testing possible factor pairs of [tex]\(8\)[/tex]:
- [tex]\(1 \cdot 8 = 8\)[/tex] and [tex]\(1 + 8 = 9\)[/tex] (does not work)
- [tex]\(2 \cdot 4 = 8\)[/tex] and [tex]\(2 + 4 = 6\)[/tex] (these are the correct numbers!)
So, the numbers that work are [tex]\(2\)[/tex] and [tex]\(4\)[/tex].
We can now write the quadratic expression as a product of two binomials:
[tex]\[ x^2 + 6x + 8 = (x + 2)(x + 4) = 0 \][/tex]
### Step 2: Solving for [tex]\(x\)[/tex]
Now, set each binomial equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x + 2 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Solving these equations:
[tex]\[ x = -2 \quad \text{and} \quad x = -4 \][/tex]
Thus, the [tex]\(x\)[/tex]-intercepts are:
[tex]\[ x = -2 \quad \text{and} \quad x = -4 \][/tex]
### Step 3: Stating the [tex]\(y\)[/tex]-Intercept
The [tex]\(y\)[/tex]-intercept of a function is the point where the graph intersects the [tex]\(y\)[/tex]-axis. This occurs when [tex]\(x = 0\)[/tex].
To find the [tex]\(y\)[/tex]-intercept, substitute [tex]\(x = 0\)[/tex] into the original equation:
[tex]\[ y = 0^2 + 6(0) + 8 = 8 \][/tex]
So, the [tex]\(y\)[/tex]-intercept is:
[tex]\[ 8 \][/tex]
### Summary
- The [tex]\(x\)[/tex]-intercepts are [tex]\(-4\)[/tex] and [tex]\(-2\)[/tex].
- The [tex]\(y\)[/tex]-intercept is [tex]\(8\)[/tex].
Thus, the detailed solutions are:
- [tex]\( x\)[/tex]-intercepts: [tex]\(-4\)[/tex] and [tex]\(-2\)[/tex]
- [tex]\( y\)[/tex]-intercept: [tex]\(8\)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.